2001
DOI: 10.1097/00004770-200105000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Correlation among Three Methods for Evaluation of Apical Leakage

Abstract: The purpose of this study was to compare three methods of evaluation of the apical seal. Thirty-six teeth were prepared with a ProFile device and filled according to three filling methods: Thermafil (n = 12), warm vertical condensation (n = 12), and the single cone technique (n = 2). The apical seal was recorded with three methods, each successively used on the same teeth: a fluid filtration method, an electrochemical method, and a dye penetration study. The three methods of evaluation did not rank the apical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0
11

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 19 publications
0
84
0
11
Order By: Relevance
“…Previous studies have emphasized that different leakage evaluation methods have little influence on study results. [24][25][26] Dye leakage testing was chosen especially for the assessment of apical leakage, and also provided an additional control for the presence of eventual cracks and fissures in the roots. The FTM chosen for the evaluation of throughand-through leakage had the advantage of re-using the same specimens for sequential leakage measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have emphasized that different leakage evaluation methods have little influence on study results. [24][25][26] Dye leakage testing was chosen especially for the assessment of apical leakage, and also provided an additional control for the presence of eventual cracks and fissures in the roots. The FTM chosen for the evaluation of throughand-through leakage had the advantage of re-using the same specimens for sequential leakage measurements.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no consensus about the methods used for leakage evaluation (9). A number of studies which evaluated the correlation between various leakage methodologies found no correlation (12)(13)(14). The lack of correlation may be related to the different physical mechanisms of the methodologies (15).…”
Section: Discussionmentioning
confidence: 99%
“…the bacterial test on the same teeth and found no correlation between the tests. Pommel et al 27 also compared fluid filtration, electro-chemical and dye leakage tests in evaluating the sealing ability of single-cone and vertical condensation obturation techniques, using the same teeth, and found no correlation among the tests. However, Wu et al 28 compared fluid filtration and dye penetration methods and found fluid transport was a more sensitive method for detecting voids along the root canal filling than dye penetration.…”
Section: Discussionmentioning
confidence: 99%